Formulation and evaluation of sustained release enteric-coated pellets of budesonide for intestinal delivery - Raval, Mihir K; Ramani, Riddhi V; Sheth, Navin R (International Journal of Pharmaceutical Investigation)
Introduction: The aim of present work was to develop intestinal-targeted pellets of Budesonide, a potent glucocorticoid, used for the treatment of ulcerative colitis and Crohn’s disease by extrusion and spheronization method. Current available oral formulations of Budesonide have low efficacy because of the premature drug release in the upper part of the gastrointestinal tract. In this study, a pH-controlled intestinal-targeted pellet of budesonide was established using 32 full factorial design by giving an enteric coating with Eudragit S100. Materials and Methods: Budesonide- sustained release pellets were prepared by extruder and spheronization technique using a combination of water-soluble and permeable polymers by applying 32 full factorial design. The pellets were coated by spray coating technique using Eudragit S100 as an enteric polymer. The pellets were characterized for its flowability, sphericity, friability, and in vitro drug release. Release behaviour was studied in different pH media. The release profile was studied for the mechanism of drug release. Result: The optimized formulation showed negligible drug release in the stomach followed by release for 12 h in the intestinal pH. Differential scanning calorimetry and Fourier Transform Infrared Spectroscopy studies indicated no interaction between drug and polymer. Scanning Electron Microscopy image of coated pellets suggested a uniform and smooth coat over the surface of pellets. Accelerated stability studies showed a stable nature of drug in the formulation. All evaluation parameter showed that pellets were good in spherocity and flowability. Conclusion: Sustained release pellets of Budesonide could be prepared by extrusion and spheronization which released the drug in intestinal pH for an intestine to treat inflammatory bowel disease. A ratio of polymer combination could be decided using a full factorial design.
Keywords: Budesonide; eudragit S100; extruder spheronizer; inflammatory bowel disease; spray coating; sustained release